Infrastruktur Jalan dan Kriminalitas di Pedesaan Indonesia - Vidyaras, Winda (Jurnal Kebijakan Ekonomi, 2022)
This study views how road infrastructure development affects crime in rural Indonesia. The issuance of Law No. 6 of 2014 concerning Villages create massive road infrastructure development to develop villages economy. However, it also create negative externality, which is crime. Using logistic regression model, this study analyzes Village Potential data for 2006-2018 in Indonesia. The results show that road infrastructure development’s accompanied by crime opportunity increase of 1.3-1.5 times higher in rural Indonesia. After massive development, it indicates economic increase and crime decrease in remote villages. This finding supports literatures about road infrastructure and accessibility can provide opportunities for crime.